Determining and Predicting the Water Demand Dynamic System Model Mapping Urban Crawling and Monitoring Using Remote Sensing Techniques and GIS (Journal of Engineering, 2018)
The problem of rapid population growth is one of the main problems effecting countries of the world the reason for this the growth in different environment areas of life commercial, industrial, social, food and educational. Therefore, this study was conducted on the amount of potable water consumed using two models of the two satellite and aerial images of the Kadhimiya District-block 427 and Al-Shu,laa district-block 450 in Baghdad city for available years in the Secretariat of Baghdad (2005, 2011,2013,2015). Through the characteristics of geographic information systems, which revealed the spatial patterns of urban creep by determining the role and buildings to be created, which appear in the picture for the year 2008, 2013, 2015, respectively, compared to buildings and residential areas allocated in 2005. Comparison of each year before to estimate the number the population is the bidder in these years. The amount of water consumed in this period has also been obtained to estimate the amount of water produced for sanitation. The knowledge of growing buildings, increasing population and percentage of increase in the amount of water consumed. Geographic information systems reveal spatial patterns of civilian creep by measuring dimensions in new urban expansion areas from city middle and roads. In various years and in order to knowledge changes that have occurred in particular in the built-up areas, and the urban analyze congestion for periods of lagging and the growth prediction of urban area in the coming years.